Improving Defect‐Based Quantum Emitters in Silicon Carbide via Inorganic Passivation. Issue 4 (5th December 2017) - Polking, Mark J.; Dibos, Alan M.; de Leon, Nathalie P.; Park, Hongkun
Abstract: Defect‐based color centers in wide‐bandgap crystalline solids are actively being explored for quantum information science, sensing, and imaging. Unfortunately, the luminescent properties of these emitters are frequently degraded by blinking and photobleaching that arise from poorly passivated host crystal surfaces. Here, a new method for stabilizing the photoluminescence and charge state of color centers based on epitaxial growth of an inorganic passivation layer is presented. Specifically, carbon antisite‐vacancy pairs (CAV centers) in 4H‐SiC, which serve as single‐photon emitters at visible wavelengths, are used as a model system to demonstrate the power of this inorganic passivation scheme. Analysis of CAV centers with scanning confocal microscopy indicates a dramatic improvement in photostability and an enhancement in emission after growth of an epitaxial AlN passivation layer. Permanent, spatially selective control of the defect charge state can also be achieved by exploiting the mismatch in spontaneous polarization at the AlN/SiC interface. These results demonstrate that epitaxial inorganic passivation of defect‐based quantum emitters provides a new method for enhancing photostability, emission, and charge state stability of these color centers. Abstract : Defect‐based quantum emitters have applications in quantum communications, sensing, bioimaging, and other areas. Improper surface termination, however, leads to blinking, photobleaching, and charge state instability. Here, a surface termination scheme based on the growth of a heteroepitaxial inorganic AlN capping layer is used to improve the photostability of carbon antisite‐vacancy pairs in 4H‐SiC and achieve spatially selective charge state control.